INOVASI PELAYANAN PUBLIK DALAM PERLINDUNGAN PEREMPUAN DAN ANAK MELALUI PROGRAM SHELTER WARGA DI KOTA MAKASSAR - Musdalifah Musdalifah; Gita Susanti (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This study aims to analyze public service innovation through the Shelter Warga Program in the protection of women and children in Makassar. The program is a community-based public service innovation developed to improve the accessibility and responsiveness of services for victims of violence. This research employed a qualitative approach with a descriptive research type. Data were collected through interviews, observations, and documentation. The informants consisted of officials from the Office of Women’s Empowerment and Child Protection, Shelter Warga administrators, and community members involved in the program. Data analysis used the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The results show that the Shelter Warga Program fulfills Rogers’ innovation characteristics, namely relative advantage, compatibility, complexity, trialability, and observability. The program has improved the quality of public services through faster, closer, and more participatory service delivery. However, the implementation still faces challenges related to limited human resources, budget constraints, and inter-agency coordination. Therefore, institutional strengthening and sustainable policy support are needed to improve program effectiveness.